Dramaturgi Emosi dan Identitas Perempuan dalam Film Garis Pilihan: Analisis Front Stage dan Back Stage pada Karakter Mila - Paramacitha, Ni Luh N. Jeylita; Handayaningrum, Warih; Rahayu, Eko Wahyuni; Sabri, Indar; Juwariyah, Anik (Universitas Syiah Kuala, 2025)
The movie Garis Pilihan tells about the journey of Mila, a girl from Sidoarjo who migrates to continue her education at Surabaya State University. Erving Goffman's dramaturgy theory and Wilhelm Wundt's structuralism theory are used to examine Mila's character dualism in the movie Garis Pilihan and real life. The purpose of this research is to see how Mila controls her emotions in the movie and real life. The research of this article uses a descriptive qualitative approach, by collecting data through observation, interviews, and literature review. The closest relatives of Mila's character served as Research informants. The findings show that although Mila is more emotional and expressive when facing various situations in the backstage, she always appears tough and strong on the frontstage. The social roles and emotional frameworks that influence Mila's character can be better understood thanks to this research. In the context of performance and everyday life, this research also presents a new perspective on the relationship between emotional control and social pressure.